Revolution in Science - Brake, M. author. aut Link
VIII, 221 p.
Keywords: This is the compelling story of the two biggest events in the evolution of ideas: the revolutions of Galileo and Darwin. Mark Brake captures the adventure and excitement of these two scientists in this is a timely examination of the ways in which faith and science clash, and how the battle for 'truth' is a perennial one.